Deradicalization through Revitalization of Religious and Nationality Insights among Indonesian Students - Muhammad Turhan Yani; Yusuf Hanafi (Edukasia Islamika, 2022)
Radicalism is part of an ideology that can grow and develop anywhere, including in colleges or universities. The study aimed to depict the phenomenon of radicalism among students by analyzing how radical influences could infiltrate students from the Islamic education lecturers' perspective. This study also examined lecturers' efforts to prevent radicalization in the campus environment. The data were collected through in-depth interviews conducted over three months. Results showed that although the campus continued to be reported by many studies as the "origin of radicalism," the situation depicted the phenomenon of radicalization at an alarming level. The Islamic education lecturers continued to confront deradicalization on campus through revitalizing religious and nationality insights. Lecturers of Islamic religious education internalize the values ​​of religious moderation to realize Islam rahmatan lil 'alamin and seek to restructure campus mosques so that they are not infiltrated by preachers with radical views.